Integrating pan-immune-inflammation value into personalized survival prediction of nasopharyngeal carcinoma: a large-scale long-term retrospective study - Wen-Chao Li; Wei-Qiong Ni; Yu-Ling Zhang; Yong-Miao Lin; Ao-Qiang Chen; Zhi-Qing Long; Si-Fen Wang; Fang-Fang Duan; Chao Zhang; Xin Huang; De-Huan Xie; Wen Xia; et al. (BMC Cancer)
Abstract Background Despite concurrent chemoradiotherapy (CCRT) being the standard treatment for locally advanced nasopharyngeal carcinoma (NPC), there remains considerable variability in survival outcomes among patients with the same tumor-node-metastasis (TNM) staging. This study aims to evaluate the prognostic significance of the pretreatment Pan-Immune-Inflammation Value (PIV), an integrative marker of immune-inflammatory status, in NPC patients undergoing CCRT. Methods A total of 860 NPC patients treated with platinum-based CCRT were included in this retrospective study. PIV was derived from pretreatment peripheral blood counts, categorizing patients into high-PIV (> 244.4) and low-PIV (≤ 244.4) cohorts. Overall survival (OS) rates were estimated using Kaplan-Meier methods and analyzed through Cox proportional hazards models. A PIV-based prognostic nomogram was developed and subsequently validated. Results Patients classified with low PIV exhibited markedly improved OS compared to those with high PIV (HR = 0.559, 95% CI: 0.415–0.753, P < 0.001). In the multivariate analysis, PIV emerged as an independent prognostic indicator, alongside age, T stage, N stage, and body mass index (BMI). Furthermore, the PIV-based nomogram demonstrated enhanced prognostic accuracy (C-index: 0.680, 95% CI: 0.641–0.719) when contrasted with the traditional TNM staging system (C-index: 0.638, 95% CI: 0.573–0.703). Conclusions The pretreatment PIV serves as an independent prognostic factor in NPC patients receiving CCRT. The nomogram founded on PIV offers improved prognostic capacity over conventional TNM staging, thereby holding potential in guiding personalized treatment strategies for this patient demographic.